Anterior Tibial Island Flap in the Management of Trophic Ulcers of Heel - G. S. Kalra; S. K. Bhatnagar; R. Chandra (Indian Journal of Plastic Surgery)
The use of anterior tibial flap as a distally based island flap for the management of trophic ulcers of heel is being presented. The advantages and vascular bases have been discussed.